Association between ventricular repolarization parameters and cardiovascular death in patients of the SWISS-AF cohort. (1st June 2022) - Rivolta, Massimo W.; Mainardi, Luca T.; Laureanti, Rita; Sassi, Roberto; Kühne, Michael; Rodondi, Nicolas; Conte, Giulio; Moschovitis, Giorgio; Schlageter, Vincent; Aeschbacher, Stefanie; Conen, David; Reichlin, Tobias; et al.
Abstract: Background: The effect of the ventricular repolarization heterogeneity has not been systematically assessed in patients with atrial fibrillation (AF). Aim of this study is to assess ventricular repolarization heterogeneity as predictor of cardiovascular (CV) death and/or other CV events in patients with AF. Methods: From the multicenter prospective Swiss-AF (Swiss Atrial Fibrillation) Cohort Study, we enrolled 1711 patients who were in sinus rhythm (995) or AF (716). Resting ECG recordings of 5-min duration were obtained at baseline. Parameters assessing ventricular repolarization were computed (QTc, Tpeak-Tend, J-Tpeak and V-index). Results: During AF, the V-index was found repeatable (no differences when computed over the whole recording, on the first 2.5-min and on the last 2.5-min segments). During a mean follow-up time of 2.6 ± 1.0 years, 90 patients died for CV reasons. In bivariate Cox regression analysis (adjusted for age only), the V-index was associated with an increased risk of CV death, both in the subgroup of patients in sinus rhythm (SR) as well as those in AF. In multivariate analysis adjusted for clinical risk factors and medications, both prolonged QTc and V-index were independently associated with an increased risk of CV death (QTc: hazard ratio [HR] 2.78, 95% CI 1.79–4.32, p < 0.001; V-index: HR 1.73, 95% CI 1.12–2.69, p = 0.014). Conclusions: QTc and V-index, measured in a single 5-min ECG recording, were independent predictors of CV death in a cohort of patients with AF and might be a valuable tool for further risk stratification to guide patient management. Clinical Trial Identifier Swiss-AF study: NCT02105844 Highlights: The V-index can be assessed in routine ambulatory 5-min ECG in patients with AF. V-index and QTc independent predictors of cardiovascular mortality in AF patients. The largest study for prognostic implications of ventricular repolarization in AF. Large ventricular repolarization heterogeneity identifies high-risk AF patients.